Impairment of Working Memory, Decision-making, and Executive Function in the First-Degree Relatives of People with Panic Disorder: A Pilot Study - Zhou, Zhenhe; Ni, Dongjie (Frontiers in Psychiatry, 2017)
Background: Panic Disorder (PD) patients present impairments of working memory, decision making and executive function. However, whether the first-degree relatives (FDRs) of PD patients present abnormal characteristics, including clinical and neuropsychological aspects, in comparison to the general population, has not been studied. Investigation and understanding of the abnormal neuropsychological characteristics of the FDRs of PD patients will contribute to the prevention and treatment of PD. Objective: The purpose of this paper is to compare the working memory, decision making and executive function among PD patients, their FDRs and controls. Materials and methods: Neuropsychological functions of 30 PD patients, 30 FDRs of PD patients and 30 controls were measured with a digit span task, Iowa Gambling Task (IGT) and Wisconsin Card Sorting Test(WCST). Results: [Please ensure that the intended meaning has been maintained in this edit.]Perseverative errors, failure to maintain set scores, and number of cards chosen from decks A, B, C, and D were higher for PD patients and their FDRs than those of controls. Furthermore, error rates for these tests were higher for PD patients than their FDRs. Forward scores and backward scores, percentage of conceptual level responses, the number of categories completed, choices from advantageous minus disadvantageous decks and mean amount of money earned of PD patients and their FDRs were all lower than those of controls. Scores for these tests were also lower for PD patients than for their FDRs. Conclusions: PD patients as well as their FDRs present different degrees of impairments of working memory, decision making and executive function. Impaired performance on three tasks appears to be associated with the diathesis for PD and may be a valuable indicator of susceptibility for this disorder.